Differential effects of N-linked glycosylation of Vstm5 at multiple sites on surface expression and filopodia formation - Lee, A-Ram; Kim, Sulgi; Ko, Kwang Woo; Park, Chul-Seung (PUBLIC LIBRARY SCIENCE, 2017)
V-set and transmembrane domain-containing protein 5 (Vstm5), a newly characterized small membrane glycoprotein, can induce membrane protrusions in various cells. Vstm5 can modulate both the position and complexity of central neurons by altering their membrane morphology and dynamics. In this study, we investigated the significance of glycosylation in the expression and function of Vstm5. Four N-linked glycosylation sites (Asn(43), Asn(87), Asn(101), and Asn(108)) are predicted to be located in the extracellular N-terminus of mouse Vstm5. Although all four sites were glycosylated, their functional roles may not be identical. N-glycosylation at multiple sites affects differentially the function of Vstm5. Glycosylation at individual sites not only played essential roles in surface expression of Vstm5 but also in the formation of neuronal dendritic filopodia. These results indicate that N-linked glycosylation at multiple sites plays important roles by differentially influencing the expression, targeting, and biological activity of Vstm5.
Keywords: RECEPTOR SUBUNITS; PROTEIN GLYCOSYLATION; DENDRITIC FILOPODIA; CELL-SURFACE; MEMBRANE; SCHIZOPHRENIA; TRANSPORTER; TRAFFICKING; SYNAPTOGENESIS; MORPHOLOGY